Subclavian steal syndrome – surgical or endovascular treatment - Cvetić, Vladimir Z; Čolić, Momčilo; Radmili, Oliver; Banzić, Igor; Končar, igor; Lukić, Borivoje; Davidović, Lazar (Vojnosanitetski pregled, 2018)
Background/Aim. A phenomenon of subclavian steal is caused by occlusion or stenosis of the proximal subclavian artery with subsequent retrograde filling of the subclavian artery via the ipsilateral vertebral artery. The aim of this research was to compare surgical method [carotid-subclavian bypass grafts (CSBG)] and endovascular methods [percutaneous transluminal angioplasty (PTA) and stenting of subclavian artery] from the aspect of immediate and long-term results. Methods. Thirty patients [16 (53.33%) males], of average age between 60.1 ± 8.25 years were treated with CSBG and compared with a group of forty patients [18 (45%) males], of the average age between  57.75 ± 6.15 years treated by PTA and stenting of subclavian artery. Immediate and long-term results were determined clinically and confirmed by Doppler pressures and duplex ultrasound/angiography. All patients were followed-up after 1, 6 and 12 months post-procedure, and annually thereafter. Results. The average follow-up for both groups was 22.37 ± 11.95 months. There were 2 (6.67%) procedural complications in the CSBG group (transient ischemic attack in 2 patients) and 3 (7.5%) ones in the PTA/stent group (dissection and distal embolization in one patient and puncture site hematoma in one patient). Systolic blood pressure difference between the two brachial arteries in CSBG group was: 42.6 ± 14.5 mmHg vs 4.75 ± 12.94 mmHg (p
Keywords: subclavian artery; subclavian steal syndrome; angioplasty; stents; blood vessel prosthesis; endovascular procedures; vascular procedures; operative